Determination of Value of Crop Factor With Corn and Cassava Using USLE Method and Small Plots on Ultisol Land in Siborongborong District of North Tapanuli - Yenci Wulandari Manik; Sumono Sumono; Nazif Ichwan; Edi Susanto (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Crop factor (C) is a factor that is easier to modify in an effort to reduce erosion. This study was aim to determine the value of crop factor of corn and cassava during July to October 2012 using USLE prediction and methods of small plots. In addition, this study was also aim to quantify the allowable erosion rate (T) and Erosion Hazard Level (TBE). Parameters measured were effective soil depth, soil permeability, levels of C-organic soil, soil texture, soil structure, and rainfall. The results showed that the value of the cassava crop factor using rainfall research data for 4 months and 12 years data were 0.68 and 0.69 respectively, and the value of the corn crop factor using rainfall research data for 4 months and 12 years data were 0.58 and 0.59 respectively. The amount of allowable erosion rate is 17.17 ton (ha.year)-1. While Erosion Hazard Rate (TBE) corn and cassava land were 0.020 and 0.024 respectively, which included in the low category. Key words: Erosion, Ultisol, Crop Factor, Siborongborong